Análise morfométrica e biodiversidade da vegetação na microbacia hidrográfica da Fazenda Experimental Edgárdia - Moreira, Lilian [UNESP] (2007)
The preservation of the biodiversity of the vegetation in the micro watershed is of basic importance for the maintenance of the animal and vegetal wild life, ambient services and protection of the biosfera. The morphometry is a tool of great importance as diagnostic of susceptibility to the ambient degradation or conservation and guides the planning and handling of the micro watershed. The present study had as objective the morphometric characterization and analysis of biodiversity in the micro watershed of the Edgárdia Farm, Botucatu - SP. The micro watershed of the Edgárdia Farm belongs to the College of Agronomicas Ciencias/UNESP, city of Botucatu - SP. The program used for the attainment of the morphometrical variable was the ILWIS 3.2 version and the topographical letter of the IBGE with 1:50.000 scale. In the study of biodiversity four transects in the micro watershed had been installed, in the parts high (superior third), medium high and medium low (medium third) and low (inferior third) of the micro watershed, in which parcels of 10 x 5 meters had been installed. In the four transects, the forest species had been quantified and commanded in popular and classified families, species, names in its respective ecological successions (pioneer, secondary or climax). It was measured in each tree the height and the diameter in the height of the chest (DAP). The morphometrical variable and the results were: area of 7,205 kmø; perimeter of 11,59 km; length and width of micro watershed 3,578 the equal 3,016 km; length of the draining net and quotas of 15,68 km and 1100,00 km; factor of form 0,79, considered very high; density of draining of 2,18 km.kmø, classified as average; the high declivity of 76,98%, in accordance with the classes of declivities and types of relief of the micro watershed, was classified as scarped; frequency of rivers the 3,19 segments of rivers... (Complete abstract click electronic access below)